Paris in color - Robertson, Nichole; Chronicle Books (Firm) (San Francisco, Calif. : Chronicle Books, 2012)
Take a journey through the world's most romantic city, travelling from colour to magnificent colour with this beguiling book.
Keywords: Color photography; Color in art; Photography, Artistic; Fotograf{acute}ia en color; Paris (France) -- Pictorial works